Analysis of Nagari Management Information System Evaluation (SIMNAG) Using PIECES and UAT Methods - Jefril Rahmadoni; Ricky Akbar; Rafiqatul Ulya (Journal of Applied Engineering and Technological Science (JAETS), 2022)
SIMNag (Nagari Management Information System) Kamang Mudiak is an information system in the nagari Kamang Mudiak. The SIMNag includes the Andalas University Service Team's web-based nagari management information system. The SIMNag menu includes a Nagari Profile, which includes information about the nagari symbol, vision and mission, organizational structure, government history, nagari history, maps of the nagari, nagari achievements, legal products, and nagari potential wealth. Furthermore, information about public information is provided, specifically nagari news related to the 11 pillars of Nagari Tageh, which include tags for health, education, food, economy, faith, bundo kanduang tags, mudo paga nagari tags, and information-based tags Digital bills, disaster bills, security and social disease bills, and law bills are all examples of bills. The developer of this application's distinctive feature, in addition to the nagari tageh feature, is the convenience feature for nagari residents to input or update their own personal and family data online. As a result, data on nagari Kamang Mudiak residents will always be updated without the need to wait for the nagari apparatus to do so. Furthermore, residents at this SIMNag can file complaints with the nagari government about anything that occurs in the vicinity of the population. It is necessary to assess the SIMNag. It is necessary to evaluate the SIMNag that has been built in order to determine the feasibility of the SIMNag application in facilitating community services. This research employs two approaches: PIECES (Performance, Information/Data, Economy, Control, Efficiency, and Security) and UAT (User Acceptance Testing). The research results in an evaluation of the system that was built, namely the nagari information system (SIMNag) in the Nagari Kamang Mudiak.